8th International Symposium on Superalloy 718 and Derivatives (2014) 2014
DOI: 10.7449/2014/superalloys_2014_587_599
|View full text |Cite
|
Sign up to set email alerts
|

Invention of a New 718-Type Ni-Co Superalloy Family for High Temperature Applications at 750°C

Abstract: In this paper the development of a new y'/ Y'-alloy on the basis of Alloy718 is presented, where the microstructure is stable at 800°C, mechanical properties are similar to Alloy718, yet do not deteriorate beyond 650°C, and the forging window is wider than the one of Alloy718, allowing for good workability. This was essentially achieved by the addition of about 17%-30% Co in combination with an Al/Ti-ratio of more than 5.0 and an Al-content of about 1.6%-2.2%. The key role of cobalt is to stabilize the 5-phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…These appeared unchanged in the bulk of the alloys after exposure at 700°C, and may be seen towards the bottom of the images in Figure 1. These two phase γ/γʹ microstructures are very similar to those found in commercial polycrystalline alloys such as Allvac®718Plus™, VDM780P and AD730® [10][11][12]. It should also be noted that some fine elongated precipitates (on the same scale as the γʹ) are visible in the bulk of Alloy 1, likely to be γʹʹ, which is known to form in alloys with elevated Nb content such as IN718 [3,82] as well as the dual-superlattice alloys that this alloy series is based on [83][84][85].…”
Section: Microstructuresupporting
confidence: 76%
See 1 more Smart Citation
“…These appeared unchanged in the bulk of the alloys after exposure at 700°C, and may be seen towards the bottom of the images in Figure 1. These two phase γ/γʹ microstructures are very similar to those found in commercial polycrystalline alloys such as Allvac®718Plus™, VDM780P and AD730® [10][11][12]. It should also be noted that some fine elongated precipitates (on the same scale as the γʹ) are visible in the bulk of Alloy 1, likely to be γʹʹ, which is known to form in alloys with elevated Nb content such as IN718 [3,82] as well as the dual-superlattice alloys that this alloy series is based on [83][84][85].…”
Section: Microstructuresupporting
confidence: 76%
“…Efforts to develop new superalloys that may supersede IN718 at comparable cost have focussed on alloys with lower Nb and higher Al contents, which favour the formation of γʹ precipitates, e.g. Allvac®718Plus TM [10], VDM®780P [11] and AD730® [12]. For further improvements to be obtained, the interrelations between the composition, processing, and microstructure on the final properties need to be understood.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, further interactions may take place in multi-component alloys not considered here. In the works of [3,23,24], a new Nb-containing wrought superalloy was developed. In this context, it was found that Co-addition increases the solvus temperature of the Nb-rich high temperature precipitates that were identified to consist of η-and δphase [25].…”
Section: Discussionmentioning
confidence: 99%